Bermudagrass Fertility Trial in Southeast Kansas, 2020 - D. Helwig; M. Haywood; J. K. Farney; B. C. Pedreira; G. F. Sassenrath (Kansas Agricultural Experiment Station Research Reports, 2021)
In 2020 a bermudagrass fertility study was conducted at the K-State Research and Extension experiment station outside of Columbus, KS. The purpose of the study was to simulate forage producer practices of managing bermudagrass and determine how each practice affects forage production and quality. Addition of fertilizer, and mowing were tested to determine the impact on forage biomass production and quality. Fertilizer increased both biomass production and forage quality. However, greater improvements in forage quality were observed by mowing the bermudagrass.
Keywords: Bermudagrass; forage; pasture; fertility; biomass production